Yoga as a therapeutic tool in autism: A detailed review - Soccalingam Artchoudane; Ananda Balayogi Bhavanani; Meena Ramanathan; Artchoudane Mariangela (Wolters Kluwer Medknow Publications, 2019)
Autism is a complex neurodevelopmental disorder affecting systems of the body and behavior. Its growth rate is approximately 3% in children. This review was undertaken to search and critically analyze the literature about musculoskeletal, cardiovascular and neurological function, and behavioral outcomes of yoga interventions for individuals with autism spectrum disorder. This systematic review has four-stage screening process and rigorous critical appraisal, which resulted in the inclusion of 36 studies. As a result, in children with autism spectrum disorder with (i) the presence of muscle weakness: yoga may decrease sympathetic activity and autonomic arousal and thereby improve handgrip strength (HGS); (ii) lowered cardiac vagal tone and elevated sympathetic tone, resulting in autonomic abnormalities including impaired language, attention, and cognition: yoga reduces blood pressure and improves attention without sympathetic activation; (iii) slower reaction times and greater standard deviations: Pranayama practice enhances central processing ability; and (iv) sensory processing issues with behavior regulations give rise to the presence of repetitive behaviors: yoga improves sensory integration, motor imitations, communications, and their own thoughts and behaviors related to physical, social, and emotional well-being. Hence, this review of clinical studies suggests that approach built on yoga intervention is worth pursuing. Desired outcomes include reduction of autism rate and improved quality of life.